Handbook of human-computer interaction - Helander, Martin, 1943-; Landauer, Thomas K.; Prabhu, Prasad V. (Amsterdam ; New York : Elsevier, 1997)
This completely revised edition, of the Handbook of Human-Computer Interaction, of which 80% of the content is new, reflects the developments in the field since the publication of the first edition in 1988. The handbook is concerned with principles for design of the Human-Computer Interface, and has both academic and practical purposes. It is intended to summarize the research and provide recommendations for how the information can be used by designers of computer systems. The volume may also be used as a reference for teaching and research. Professionals who are involved in design of HCI will find this volume indispensable, including: computer scientists, cognitive scientists, experimental psychologists, human factors professionals, interface designers, systems engineers, managers and executives working with systems development. Much of the information in the handbook may also be generalized to apply to areas outside the traditional field of HCI.
pt. 1. Issues, theories, models and methods in HCI -- pt. 2. Design and development of software systems -- pt. 3. User interface design -- pt. 4. Evaluation of HCI -- pt. 5. Individual differences and training -- pt. 6. Multimedia, video and voice -- pt. 7. Programming, intelligent interface design and knowledge-based systems -- pt. 8. Input devices and design of work stations -- pt. 9. CSCW and organizational issues in HCI.
Includes bibliographical references and indexes.
Print version record.
WorldCat record variable field(s) change: 650
Keywords: Human-computer interaction -- Handbooks, manuals, etc; Human beings; Humans; User-Computer Interface; Computers; Interaction personne-ordinateur -- Guides, manuels, etc; Êtres humains; Ordinateurs; Homo sapiens (species); computers; COMPUTERS -- Interactive & Multimedia; COMPUTERS -- Social Aspects -- Human-Computer Interaction; Human-computer interaction; Mens-computer-interactie.; Software; Systeemontwerp; Computernetwerken; handbooks; Handbooks and manuals; Handbooks and manuals; Guides et manuels